Research on the Promotion Path of Regional Public Brand Empowerment: Taking ’Nan Xi Jia Pin’ in Yongjia County of Wenzhou City as an example - Wang, Xiaoyu; Lai, Sitong; Gao, Yuli; Chen, Gaoxiang; Chen, Jiayi; Ma, Yuxing (International Journal of Global Economics and Management, 2024)
The purpose of this paper is to explore the basic role of national poverty alleviation support in rural revitalization, especially in areas such as Yongjia County, which is faced with the problems of small per capita cultivated land area, heavy business and light agriculture in the industrial pattern, and insufficient development of agricultural economic advantages. This paper points out that Yongjia County needs to carry out in-depth professional investigation and research on the empowerment and promotion of public brands to analyze the current situation and problems of the industry, and combine local characteristic culture with rural industry to provide accurate services for the local area. In this context, the ’ Nan Xi Jia Pin ’ Yongjia County Public Brand Empowerment Promotion Strategy is proposed. This strategy not only helps to promote Yongjia ’s economic development, promote local characteristic culture, improve public brand efficiency, avoid repeated investment, but also brings learning and communication opportunities covering multiple fields for rural agricultural industries. In addition, the strategy can also strengthen cooperation and resource sharing between Yongjia and other developing villages, and show the country Yongjia ’s simple cultural characteristics, ideas and models. Therefore, the development of Yongjia county public brand empowerment is urgent and important. In order to provide useful reference for the construction and development of regional public brands of agricultural products in other regions.